ANALISIS KASUS ROCKY GERUNG YANG DIDUGA MELAKUKAN PENGHINAAN TERHADAP PRESIDEN JOKOWI DODO - Nata , Maria Alfira; Nanga, Antonia Alfiayu Zigha; Moa , Lousiano Grandiroyvan Wera; Arman, Yohanes (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
This study analyzes the case of insult against President Jokowi Dodo by Rocky Gerung, an intellectual and critic of the government. This study uses a qualitative method with a case study approach, which allows the researcher to understand the phenomenon from various aspects. Qualitative data were collected from various sources, such as mass media, social media, and legal documents. This study uses the Differential Association theory and the Labelling theory to explain Rocky Gerung's behavior. The results of the study show that Rocky Gerung's statement has the potential to be considered as insulting the president personally, even though he claims to be a critique of the government's policy. Insulting the leader of the state should not be done in the space of democracy and freedom of expression. As an intellectual, Rocky Gerung should express his opinion with responsibility and respect for public institutions.